2014
DOI: 10.3109/13506129.2013.876984
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical amyloidosis associated with subcutaneous insulin and enfuvirtide administration

Abstract: Protein and peptide drugs administered subcutaneously, such as insulin can be amyloidogenic and result in localized amyloid deposits at the sites of medication injections. These iatrogenic amyloidoses typically present as a localized subcutaneous nodule or skin reaction at the site of administration, and often pose diagnostic challenges. We have analyzed the amyloid proteome in 52 cases of insulin and enfuvirtide associated amyloidosis using laser microdissection/tandem mass spectrometry. We show that the depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 19 publications
0
67
0
1
Order By: Relevance
“…It was reported that in patients with LIDA, there was an equal distribution of Type 1 and Type 2 diabetes . LIDA predominantly affects male patients, with a sex ratio of about 2 : 1 . The average age of male and female patients with LIDA in the study was similar (59.8 and 56.5 years, respectively) …”
mentioning
confidence: 51%
See 1 more Smart Citation
“…It was reported that in patients with LIDA, there was an equal distribution of Type 1 and Type 2 diabetes . LIDA predominantly affects male patients, with a sex ratio of about 2 : 1 . The average age of male and female patients with LIDA in the study was similar (59.8 and 56.5 years, respectively) …”
mentioning
confidence: 51%
“…LIDA predominantly affects male patients, with a sex ratio of about 2 : 1 . The average age of male and female patients with LIDA in the study was similar (59.8 and 56.5 years, respectively) …”
mentioning
confidence: 55%
“…In addition, d-AQuA might be of practical use for the detection of even the smallest traces of insulin aggregates that cannot be detected with existing analytical methods in biopharmaceutical preparations of insulin products used for therapy in diabetes patients 4749 and may lead to an immune response in patients after subcutaneous injection. 49 Our technology also holds the potential to be used for rapid, ultrasensitive and highly parallel preclinical and clinical diagnosis through the detection of early pathological propagons in protein misfolding and aggregation (PMA) diseases for personalized medicine. In particular, a small-volume, single-use disposable chip with the ability to diagnose accurately PMA diseases from body fluids holds great promise for novel automated diagnostic approaches.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent construction of the network incorporated only well-characterized in vivo amyloidogenic proteins, published by Sipe et al [2], excluding Enfurvitide an anti-retroviral peptide drug [43], as well as Immunoglobulin Light and Heavy Chains. In the case of Immunoglobulin chains (e.g.…”
Section: Methodsmentioning
confidence: 99%